English language attrition in short conversation and passage listening comprehension. - Yu, Zhonggen; Chan, Swee Heng (Asian EFL Journal Press, 2009)
The purpose of this study is to examine whether language attrition in both short conversation and passage listening comprehension occurs among tertiary students. The number of the participants is 359, who are all from Nanjing University of Posts & Telecommunications. A test paper, adapted from China’s College English Test Band Six, was used as the instrument to measure participants’ short conversation and passage listening comprehension before and after the two-month holiday. The result indicates that participants’ short conversation listening comprehension improved significantly and obviously over the holiday. However, no statistical significance was found in passage listening comprehension. The reasons for the results were also analyzed and discussed.